The Effect of Earnings Per Share (EPS), Debt to Equity Ratio (DER), and Return on Equity (ROE) on Stock Prices - Diaz Bayu Samudra; Zaharuddin Zaharuddin; Supriyadi Supriyadi (Applied AI and Machine Learning Journal, 2026)
Purpose: This study examines the effect of Earnings Per Share (EPS), Debt to Equity Ratio (DER), and Return on Equity (ROE) on the stock prices of state-owned enterprises listed on the Indonesia Stock Exchange from 2020 to 2024. Research Methodology: Using purposive sampling, 16 firms were selected from a pool of 20, and data were collected over five years. This research employed descriptive and verification methods, analyzing secondary data through regression, correlation, F-test, t-test, and determination analyses to test the hypotheses. Results: The findings reveal that EPS, DER, and ROE simultaneously influence stock prices, with EPS having a positive significant effect and DER and ROE showing significant negative effects. Conclusions: This study concludes that EPS is a crucial factor in determining stock prices, while high DER and ROE may negatively impact investor perception. Limitations: This study is limited by its focus on state-owned enterprises, which may not represent the broader market, and by its reliance on secondary data, which could introduce reporting biases. Contributions: The findings provide valuable insights for investors and policymakers on the key financial indicators affecting stock prices, emphasizing the importance of monitoring EPS, DER, and ROE in evaluating the financial health of state-owned companies.